Neuroactive steroids and their role in epilepsy - Patil, Chetan Y.; Jadhav, Shamsundar A.; Doifode, Sudhakar M.; Baig, Mirza Shiraz (International Journal of Basic & Clinical Pharmacology, 2017)
Neuroactive steroids are the certain steroids that alter neuronal excitability via the cell surface through interaction with certain neurotransmitter receptors. Neuroactive steroids regulate physiological functions of the central nervous system and have possible therapeutic potential in neurological diseases. They have been shown to affect neuronal excitability via their interaction with the ligand-gated ion channel family, such as the GABAA receptor by acting genomically as well as nongenomically. Positive modulators of GABAA receptor have anticonvulsant action as they enhance GABAergic transmission thereby increasing the seizure threshold. By virtue of these properties, neurosteroids appear to be relevant to pathophysiology and pharmacological treatment of many neurological diseases including catamenial epilepsy, stress induced epilepsy, temporal lobe epilepsy, alcohol withdrawal seizures, infantile spasm and status epilepticus. So far, only synthetic neurosteroid, ganaxolone has been tried in treatment of epilepsy and has shown good efficacy and tolerability. But, human data of trials are limited and hence, large double-blinded, placebo-controlled, randomized clinical trials are required before their use. The paper reviews the biosynthesis and GABAA receptor modulation of neurosteroids and their potential role in epilepsy.